Respuesta :
let's say that the first number is x
the second is y
and the third is z
we start off with the equation that the sum of the three number is 45
[tex] x + y + z = 45 [/tex]
the "second of the three numbers is three more than twice the first number" means that
[tex] y = 2x + 3 [/tex]
the "third number is two more than the first number" means that
[tex] z = x + 2 [/tex]
we plug [tex]y[/tex] and [tex]z[/tex] back into the first first equation and get
[tex] x + (2x+3) + (x+2)=45 [/tex]
assuming you are missing an addition sign in your option C
your answer would be C. x+(2x+3)+(x+2)=45
the second is y
and the third is z
we start off with the equation that the sum of the three number is 45
[tex] x + y + z = 45 [/tex]
the "second of the three numbers is three more than twice the first number" means that
[tex] y = 2x + 3 [/tex]
the "third number is two more than the first number" means that
[tex] z = x + 2 [/tex]
we plug [tex]y[/tex] and [tex]z[/tex] back into the first first equation and get
[tex] x + (2x+3) + (x+2)=45 [/tex]
assuming you are missing an addition sign in your option C
your answer would be C. x+(2x+3)+(x+2)=45